Pengembangan Terapi Regeneratif pada Osteoartritis Sendi Temporomandibula : Telaah Pustaka - Robin, Dwi Merry Christmarini (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2024)
Temporomandibular joint osteoarthritis (TMJ OA) is a degenerative condition that affects the temporomandibular joint, causing pain, stiffness, and limited jaw movement. Conventional therapies such as medications, physical therapy, and surgery often only provide temporary solutions and cannot permanently restore joint function. Therefore, regenerative therapy has emerged as a promising approach to address TMJ OA by harnessing the body's natural healing potential. This literature review aims to provide a comprehensive overview of the development of regenerative therapies for TMJ OA, including therapeutic strategies, challenges, and future opportunities. Regenerative therapies for TMJ OA encompass various strategies, such as stem cell injections, biomaterial scaffolds, growth factors, gene therapy, and combination therapies. Although regenerative therapies have shown promising results in preclinical studies, several challenges remain, such as safety, efficacy, and translation into clinical applications. It can be concluded that regenerative therapy offers an innovative and potential approach to addressing TMJ OA by utilizing the body's natural healing capabilities, with the hope of restoring joint function and improving the quality of life for TMJ OA patients in the future.